Default Settlement on Unsecured Loans - Kuntri Selvilia Lidya Sari; Tutiek Retnowati (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2022)
Economic development is the most important part of national development goals, such as the 1945 Constitution (after amendments) in the fourth paragraph, namely: Protecting the entire nation to promote general welfare, educating the nation's life and participating in carrying out world order. The aim is to find out and analyze the legal consequences arising from Default from a credit agreement without collateral and to know and analyze so that the settlement of default from an unsecured credit agreement is carried out by the debtor. The research method used is normative law (normative juridical) and analysis of laws and regulations, jurisprudence, contracts and legal literature. The result of the research is the position of guarantee in providing credit by the Bank as the creditor to the debtor, which is an absolute requirement with the aim of having legal certainty which has been expressly regulated in the credit agreement. Legal remedies that arise if credit is given without any guarantee from the customer (debtor) is that the bank is in its position as a concurrent creditor on a par with other creditors in terms of paying off credit debts, so that they have to compete with other creditors in paying off credit debts. Because it does not